Anne of Green Gables - West, Clare; Simpson, Kate.; Montgomery, L. M., (Lucy Maud), 1874-1942. (Oxford : Oxford University Press, 2008)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
"First published in Oxford Bookworms, 1994 ; This simplified edition, Oxford University Press, c2008"--T.p. verso.
Keywords: Readers (Elementary); Readers (Secondary); Reading comprehension -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; Orphans -- Prince Edward Island -- Juvenile literature; Friendship -- Prince Edward Island -- Juvenile literature; Country life -- Prince Edward Island -- Juvenile literature